Drug Interaction Potency on Type 2 Diabetes Mellitus Patient in Hospital X in South Tangerang - Yardi Saibi; Delina Hasan; Verona Shaqila (Faculty of Pharmacy, Universitas Gadjah Mada)
Drug interaction is an interaction among a drug with other ingredients that prevents the drug from giving certain or expected effect. Such interaction might happen between a drug and other drugs, drugs with food, as well as drugs and disease. Potential drug interaction in patients with type 2 diabetes mellitus in some hospitals had been reported by several previous publications. This study aimed to identify the potential of drug interactions in patients with type 2 diabetes mellitus at Hospital X, South Tangerang. This paper is a descriptive research with retrospective retrieval data. Data were obtained in the form of patient medical records from July 2014 to June 2015. Data analysis was done by descriptive statistic analysis using SPSS version 16. The results showed that there were 90 medical records that fulfilled the inclusion criteria. Of these, 57.7% was found to be potential drug interaction. There are 55 drug interactions that potentially cause hypoglycemia, and there are 21 times that potentially cause hyperglycemia. The severity of interaction in moderate category was 89.39% (total of 66), and the rest was in minor category. Major categories were not found. The potential for drug interactions in type 2 diabetes mellitus patients is quite common and these findings complement the findings of previous published studies. Physicians and pharmacists as health workers who are directly related to the treatment of patients need to increase awareness of the potency of interactions of these drugs.